Description of four new species of Lamiinae (Coleoptera: Cerambycidae) from Panama - Lanuza-Garay, Alfredo; Rivera, Marleny (Zootaxa, 2024)
Four new species of Lamiinae from Panama are described: Sternacutus akersae sp. nov.; Trichotithonus barrocoloradensis sp. nov.; Pseudosparna carmenae sp. nov. (Acanthocinini); and Piriana aielloae sp. nov. (Colobotheini).